Understanding the phase and solvation behavior of fluorinated ionic liquids - Ferreira, Margarida L. (2022)
the contract of Individual Call to Scientific Employment Stimulus 2021.01432.CEECIND (A.B.P.) Additional partial support has been provided by Khalifa University of Science and Technology through project RC2-2019-007. Publisher Copyright: © 2022 The Authors